2020
DOI: 10.1186/s12943-020-01179-5
|View full text |Cite
|
Sign up to set email alerts
|

A novel protein encoded by circFNDC3B inhibits tumor progression and EMT through regulating Snail in colon cancer

Abstract: Background Colon cancer (CC) is a common malignant cancer. Recently, circFNDC3B was found to exert biological function in multiple cancers. However, it was unclear whether the potential protein encoded by circFNDC3B is involved in carcinogenesis of CC. Methods We used Sanger sequence and RNase R digestion assay to confirm the existence of circFNDC3B, and quantitative real-time PCR was used to evaluate the circRNA’s expression. Then fluorescence in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
155
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 173 publications
(158 citation statements)
references
References 30 publications
1
155
1
1
Order By: Relevance
“…In consequence, it relieves the inhibitory effects of miRNA on downstream target genes, thus upregulating the expression levels of the target genes [ 8 ]. Furthermore, some circRNAs exert biological functions via binding to RNA-binding proteins or translating into proteins [ 9 , 10 ]. Previous studies indicated that circRNAs are involved in regulation of autophagy in several diseases such as breast cancer, sciatic nerve injury, and cerebral ischemic stroke [ 11 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…In consequence, it relieves the inhibitory effects of miRNA on downstream target genes, thus upregulating the expression levels of the target genes [ 8 ]. Furthermore, some circRNAs exert biological functions via binding to RNA-binding proteins or translating into proteins [ 9 , 10 ]. Previous studies indicated that circRNAs are involved in regulation of autophagy in several diseases such as breast cancer, sciatic nerve injury, and cerebral ischemic stroke [ 11 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…A1, Zeiss, Oberkochen, Germany). The scratch distance at 48 h was subtracted from the scratch distance at 0 h to calculate the percentage closure of the wound [29]. The average distance of migration reflects the cell migration capacity.…”
Section: Evaluation Of Cell Migration and Invasionmentioning
confidence: 99%
“…A1, Zeiss, Oberkochen, Germany). The scratch distance at 48 h was subtracted from the scratch distance at 0 h to calculate the percentage closure of the wound [29]. The average distance of migration re ects the cell migration capacity.…”
Section: Evaluation Of Cell Migration and Invasionmentioning
confidence: 99%